Robust and cost-saving static solid cultivation method for lipid production using the chlamydospores of Phanerochaete chrysosporium - Liu, Lei (2019)
Background : During current submerged fermentation for microbial lipid production, the large-scale reactor operations inevitably consume substantial amounts of water and electricity for aeration, stirring, and temperature control and result in the operational costs almost exceeding the biodiesel value produced. Thus, developing a novel low-cost cultivation strategy is urgently needed by microbial lipid industry. Results : The filamentous fungus Phanerochaete chrysosporium can synthesize and accumulate lipids via static solid cultivation. The conversion efficiency of substrates to lipids reaches 0.277 g/g substrate after optimization of the following cultivation factors: humidity, solid medium thickness, temperature, and rotary speed. The lipids obtained by static solid cultivation differ in component and relative content from those achieved by submerged cultivation. Laser scanning confocal microscopy reveals that numerous chlamydospores filled with lipids appear during static solid cultivation, and the fungal morphological change explains why static solid cultivation is superior in lipid yield compared with submerged fermentation. The genes coding the enzymes related to fatty acid elongation and degradation are differently expressed during static solid cultivation, which presents an answer to the appearance of abundant saturated long-chain fatty acids (93.6% in total fatty acids) in chlamydospores. In addition, engineering viability and cost–benefit analysis show that the conversion of wheat bran and glucose to lipid by the fungus is efficient. More importantly, the solid cultivation incurs only a small reactor operational cost because neither cooling water nor electrical equipment, including aerator, stirrer, and the temperature control system, is used. Conclusions : This study developed a robust and cost-saving solid fermentation method without an aerator, stirrer, and temperature control system to produce microbial lipids using the chlamydospores of P. chrysosporium. Compared with conventional submerged fermentation, the solid cultivation strategy is promising because it diminishes most of the reactor operational costs, including water and power expenses.